2010
DOI: 10.2341/10-114-l
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxalate Desensitizers on the Microleakage of Resin Composite Restorations Bonded by Etch and Rinse Adhesive Systems

Abstract: ©Operative Dentistry, 2010, 35-6, 682-688 F Shafiei • M Motamedi AA Alavi • B Namvar Clinical RelevanceThe effect of oxalate desensitizer application after acid etching on the dentinal marginal sealing ability of resin composite restorations may be adhesive-specific. SUMMARYThis in vitro study evaluated the effect of an oxalate desensitizer (OX) on the marginal microleakage of resin composite restorations bonded by two three-step and two two-step etch and rinse adhesives. Class V cavities were prepared on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionsupporting
confidence: 64%
“…The coverage of the dentin surface with an acid-resistant layer of oxalate crystals may interfere with the formation of a sufficient hybrid layer, decreasing the bond strength to dentin [30]. In addition, they also believe that although the oxalate solution has been thoroughly rinsed before the adhesives' application, residual oxalic acid may have remained and reacted with calcium, causing crystal precipitation on the dentin surface, which, in turn, could disturb polymerization of the adhesives and, ultimately, compromise their bonding performance [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Shafie et al [32] reported that oxalate desensitizer adversely influenced the marginal sealing ability of composite restorations. In the light of the obtained results, BisBlock desensitizer has no positive effect on the marginal microleakage in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mineral deposits at the base of the exposed collagen matrix might fill the resin‐free gaps of the hybrid layer that might decrease the permeability and enhance the polymerization of resin cements. Lowering the risk of nanoleakage and improving the bond durability might be expected …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CPP‐ACP application in combination with OS/Duolink showed compromised results. The OS adhesive is less acidic (pH = 4.61) than Ex DSC and contains fluoride (806 ppm) . The formation of calcium fluoride (CaF 2 ) spherical globules following interaction of the free fluoride ions in the OS adhesive and available calcium and phosphate ions on the dentin surfaces after CPP‐ACP treatment plus the limited dissolving capacity of OS adhesive because of low acidity might interfere with resin infiltration and decrease the SBS of OS/Duolink.…”
Section: Discussionmentioning
confidence: 99%